INVESTIGATION OF FORCE AND MOMENT EFFECT OF ST 37 AND ST 70 ROOF LATTICE STEELS IN ANSYS PROGRAM - Zengin, Bilgin; Taşkaya, Semih; Kaymaz, Kürşat (Bilal GÜMÜŞ, 2018)
St 37 and St 70 steels are materials used in the manufacturing of general building materials, produced by processing the hot-formed steel further through a cold drawing process. Finite element method helps simplifying complex engineering problems and solving them with controllable parts. The roof  lattice model simulated in the present study is a 4-surface pyramidal roof which is 4 mm in diameter, 0.5 mm in thickness and it is designed in 3D in Ansys software by using the finite element method. The bottom corner nodes of the roof lattice model are stabilized and the vector stress effects of 65.000 N force applied in  Fx, Fz directions and 75.000 N force applied in Fy direction on the top node truss axes, 65.000 N.m moment applied in Mx, Mz directions and 75.000 N.m moment applied in My direction on middle truss nodes are investigated. According to the test results in Ansys software, vector stress increase due to both force and moment effect in truss axes of the St 70 lattice roof steel compared to the St 37 steel.
Keywords: Engineering; Mühendislik